1997
DOI: 10.1103/physrevd.56.4745
|View full text |Cite
|
Sign up to set email alerts
|

Geometric structure of the generic static traversable wormhole throat

Abstract: Traversable wormholes have traditionally been viewed as intrinsically topological entities in some multiply connected spacetime. Here, we show that topology is too limited a tool to accurately characterize a generic traversable wormhole: in general one needs geometric information to detect the presence of a wormhole, or more precisely to locate the wormhole throat. For an arbitrary static spacetime we shall define the wormhole throat in terms of a 2-dimensional constant-time hypersurface of minimal area. (Zero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
371
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(382 citation statements)
references
References 9 publications
7
371
0
4
Order By: Relevance
“…For the case of static wormholes the throat is defined as a minimal area surface satisfying a flare-out condition [3]. To fulfill this, wormholes must be threaded by exotic matter that violates the null energy condition [1][2][3][4]; it was shown by Visser et al [5], however, that the amount of exotic matter needed around the throat can be made as small as desired by means of an appropriate choice of the geometry of the wormhole.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of static wormholes the throat is defined as a minimal area surface satisfying a flare-out condition [3]. To fulfill this, wormholes must be threaded by exotic matter that violates the null energy condition [1][2][3][4]; it was shown by Visser et al [5], however, that the amount of exotic matter needed around the throat can be made as small as desired by means of an appropriate choice of the geometry of the wormhole.…”
Section: Introductionmentioning
confidence: 99%
“…In General Relativity, they are threaded by matter that violates the null energy condition [1][2][3][4][5]; the amount of this exotic matter can be made arbitrary small [6], but at the expense of large pressures at the throat [7]. Traversable wormholes can be constructed [2] by cutting and pasting two manifolds to form a new one, with a shell at the joining surface corresponding to the throat, where the flare-out condition is fulfilled.…”
Section: Introductionmentioning
confidence: 99%
“…The throat is defined as a minimal area hypersurface which satisfies a flare-out condition [3]. This requires the presence of exotic matter, that is, matter which violates the null energy condition (NEC) [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The throat is defined as a minimal area hypersurface which satisfies a flare-out condition [3]. This requires the presence of exotic matter, that is, matter which violates the null energy condition (NEC) [1,2,3,4]. Because it has been shown that the amount of exotic matter necessary for the existence of a wormhole can be made infinitesimally small by a suitable choice of the geometry [5], considerable efforts have been addressed to precisely quantify such amount for different configurations, and to show how it can be minimized [6].…”
Section: Introductionmentioning
confidence: 99%